2020
DOI: 10.3390/en13040944
|View full text |Cite
|
Sign up to set email alerts
|

New Dispatching Paradigm in Power Systems Including EV Charging Stations and Dispersed Generation: A Real Test Case

Abstract: Electric Vehicles (EVs) are becoming one of the main answers to the decarbonization of the transport sector and Renewable Energy Sources (RES) to the decarbonization of the electricity production sector. Nevertheless, their impact on the electric grids cannot be neglected. New paradigms for the management of the grids where they are connected, which are typically distribution grids in Medium Voltage (MV) and Low Voltage (LV), are necessary. A reform of dispatching rules, including the management of distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Several studies have investigated how the presence of DGs and power electronics based on non-linear loads influence power quality in low-voltage grids and how the negative effects can be mitigated [1][2][3][4][5][6][7]. The study reported in [8] states that the uncontrolled charging of PEVs has negative effects on network demand, voltage unbalance factor (VUF), and the voltage profile of the LV distribution grid, while [9] lists line congestion, voltage drops, inverse power flows, increased energy losses, and power quality (PQ) as problems related to DG and PEV charging stations. stability question, other issues remain in the voltage domain-mainly in the field of electrical power quality.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated how the presence of DGs and power electronics based on non-linear loads influence power quality in low-voltage grids and how the negative effects can be mitigated [1][2][3][4][5][6][7]. The study reported in [8] states that the uncontrolled charging of PEVs has negative effects on network demand, voltage unbalance factor (VUF), and the voltage profile of the LV distribution grid, while [9] lists line congestion, voltage drops, inverse power flows, increased energy losses, and power quality (PQ) as problems related to DG and PEV charging stations. stability question, other issues remain in the voltage domain-mainly in the field of electrical power quality.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of the study [8] work on a real case by monitoring an electric bus fleet and analyzing the direct and indirect environmental aspects impacting the emission and health of citizens in Cluj-Napoca, Romania. Study [9] presents a new paradigm regarding Electric Vehicles (EVs) and the management distribution grids. Concerning Energy management, study [13], addresses the charging requests by considering a battery swap solution, achieving a long-distance trip addressing the challenges of developing appropriate swap battery methods for a large number of EVs with charging demands while also taking into account the variance in the battery charging rate.…”
Section: Introductionmentioning
confidence: 99%
“…Study [9] presents a new paradigm regarding Electric Vehicles (EVs) and the management distribution grids. Concerning Energy management, study [13], addresses the charging requests by considering a battery swap solution, achieving a long-distance trip addressing the challenges of developing appropriate swap battery methods for a large number of EVs with charging demands while also taking into account the variance in the battery charging rate.…”
Section: Introductionmentioning
confidence: 99%